Pneumatic retinopexy for treatment of posterior pole detachment following vitreoretinal surgery for diabetic tractional retinal detachment threatening the fovea - Bastion, Mae-Lynn Catherine (BMJ Case Rep, 2012)
To describe the usage of 100% perfluoropropane and subsequent laser retinopexy for the repair of posterior pole retinal detachment in a previously vitrectomised patient with diabetic tractional detachment.